2018
DOI: 10.1371/journal.pone.0206933
|View full text |Cite
|
Sign up to set email alerts
|

Association between PR interval prolongation and electro-anatomical substrate in patients with atrial fibrillation

Abstract: BackgroundAtrial fibrillation (AF) is the most common sustained arrhythmia in clinical routine. Left atrial (LA) electro-anatomical remodelling in AF patients indicates disease progression and is associated with poor therapeutic success. PR interval prolongation is associated with an increased risk for AF, however, the association between LA remodelling measured as low voltage areas (LVA) during catheter ablation and PR interval is unknown. The aim of this study was to investigate the association between PR in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
1
8
0
1
Order By: Relevance
“…A significant correlation between PR interval prolongation and AF recurrence after radiofrequency ablation was also shown [15]. Furthermore, Schumacher et al recently demostrated that PR interval prolongation is associated with electro-anatomical substrate in AF patients, assuming that PR interval could be used as a marker for atrial remodelling before catheter ablation [16].…”
Section: Discussionmentioning
confidence: 99%
“…A significant correlation between PR interval prolongation and AF recurrence after radiofrequency ablation was also shown [15]. Furthermore, Schumacher et al recently demostrated that PR interval prolongation is associated with electro-anatomical substrate in AF patients, assuming that PR interval could be used as a marker for atrial remodelling before catheter ablation [16].…”
Section: Discussionmentioning
confidence: 99%
“… 16 From these parameters, the PR interval can be defined as the time needed to conduct electrical impulses from the sinoatrial node to the atrioventricular node, and its prolongation has been related to the remodeling of atria and thus with an increased incidence of AF. 17 One of the new predictors of new-onset AF was demonstrated by a meta-analysis study. They observed that individuals who have frequent premature atrial contractions recorded by Holter monitoring or 12-lead electrocardiogram were at a 3-fold greater risk of new-onset AF than individuals without premature atrial contractions.…”
Section: Increasing Height Alters Atrial Dimensions and Conduction Pamentioning
confidence: 99%
“…We observed PQ interval shortening after 5 weeks of HFFD in all groups (except HFFD 5+3 group), but there were no further changes either after another 3 weeks of the diet or after venlafaxine administration. Even though PQ interval prolongation is considered a risk factor for the development of atrial fibrillation (Schumacher et al, 2018), short PQ interval may be observed due to conduction abnormalities in the atrioventricular node and/or His-Purkyne network and may predispose the individuals to dysrhythmias (Moro & Cosio, 1980). PQ interval was found to be shortened in obese patients with no cardiovascular disease (Bilora et al, 1999).…”
Section: Discussionmentioning
confidence: 99%